Assessing Differential Binding of Aggregation-Induced Emission-Based Luminogens to Host Interacting Surface Proteins of SARS-CoV-2 and Influenza Virus–An in silico Approach - Karunakar Tanneeru (Frontiers Media S.A., 2021)
Early detection of asymptomatic cases through mass screening is essential to constrain the coronavirus disease 2019 (COVID-19) transmission. However, the existing diagnostic strategies are either resource-intensive, time-consuming, or less sensitive, which limits their use in the development of rapid mass screening strategies. There is a clear pressing need for simple, fast, sensitive, and economical diagnostic strategy for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) screening even in resource-limited settings. In the current work, we assessed the in silico feasibility of directly labeling virus surface proteins using fluorogenic molecules with aggregation-induced emission (AIE) property. Here, we present the results for binding of two such AIE probes, phosphonic acid derivative of tetraphenyl ethylene (TPE-P) and sulfonic acid derivative of tetraphenyl ethylene (TPE-S), to SARS-CoV-2 spike protein based on in silico docking studies. Our results show that both TPE-P and TPE-S bind to angiotensin converting enzyme 2 (ACE2)-binding, and N-terminal domains of SARS-CoV-2 spike protein. Molecular dynamic simulations have revealed specific nature of these interactions. We also show that TPE-P and TPE-S bind to hemagglutinin protein of influenza virus, but the interaction strength was found to be different. This difference in interaction strength may affect the emission spectrum of aforementioned AIE probes. Together, these results form a basis for the development of AIE-based diagnostics for differential detection of SARS-CoV-2 and influenza viruses. We believe that these in silico predictions certainly aid in differentially labeling of the both viruses toward the development of rapid detection by AIE probes.